Influence of Strategic Knowledge Management on Firm Innovativeness and Performance - Guillermo Davila (FUCAPE Business School, 2019)
This paper identifies the type and intensity of relationships that exist between strategic knowledge management (SKM) practices, innovation performance and organizational Performance. By doing so, it covers theoretical gaps about the analysis of these relationships in emerging countries. Data was collected from a sample composed by 127 Southern Brazilian firms and PLS-SEM was used for testing the hypotheses. The relevance of SKM practices for innovation and organizational performance is supported. The research has also shown the level of efficiency and use of each SKM practice. The findings allow Brazilian practitioners to identify those actions which stronger influence on innovativeness and performance. The results also have shown that Brazilian firms are focused on management of explicit knowledge, and there are some opportunities for improving performance if they focus more on tacit knowledge. The suggestions about priority practices and managing of tacit knowledge are relevant contributions to support managerial decisions for resource allocation oriented to improve innovation and performance.